2011
DOI: 10.1175/jamc-d-11-019.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enhanced Satellite-Derived Atmospheric Motion Vector Observations on Numerical Tropical Cyclone Track Forecasts in the Western North Pacific during TPARC/TCS-08

Abstract: Enhanced atmospheric motion vectors (AMVs) produced from the geostationary Multifunctional Transport Satellite (MTSAT) are assimilated into the U.S. Navy Operational Global Atmospheric Prediction System (NOGAPS) to evaluate the impact of these observations on tropical cyclone track forecasts during the simultaneous western North Pacific Ocean Observing System Research and Predictability Experiment (THORPEX) Pacific Asian Regional Campaign (TPARC) and the Tropical Cyclone Structure-2008 (TCS-08) field experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…This is done because assimilating many high-resolution observations, which represent small-scale variability the model cannot resolve, can introduce noise into the model and degrade the solution. Furthermore, the assimilation scheme assumes observation errors to be uncorrelated, and the super-obbing process reduces any such correlations that might exist, as well as reducing random error (Berger et al, 2011;Purser et al, 2000).…”
Section: Quality Controlmentioning
confidence: 99%
“…This is done because assimilating many high-resolution observations, which represent small-scale variability the model cannot resolve, can introduce noise into the model and degrade the solution. Furthermore, the assimilation scheme assumes observation errors to be uncorrelated, and the super-obbing process reduces any such correlations that might exist, as well as reducing random error (Berger et al, 2011;Purser et al, 2000).…”
Section: Quality Controlmentioning
confidence: 99%
“…Techniques for assimilation of geostationary satellite data with high temporal resolution have been improving in recent years (Munro et al 2004;Peubey and McNally 2009;Berger et al 2011;Okamoto 2013;Wu et al 2014). Yamashita (2010) reported that track forecast errors for typhoon SINLAKU were reduced by 9 %-12 % on average by the assimilation of RS-AMVs in the experiments conducted during the THORPEX Pacific Asian Regional Campaign 2008 (Nakazawa et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Aberson also noted that storms not targeted with special observations could be impacted by dropwindsondes in other systems, as the influence of the dropwindsonde data propagates globally through the update cycle, and due to the spectral nature of the system. Berger et al (2011) examined the impact of enhanced satellite-derived atmospheric motion vectors (AMVs), as well as dropwindsonde data, on T-PARC TC forecasts in the Navy forecast system. [For a description of satellite products made available during T-PARC/TCS-08, please see Hawkins and Velden (2011).]…”
Section: Introductionmentioning
confidence: 99%